1994
DOI: 10.1161/01.hyp.23.2.229
|View full text |Cite
|
Sign up to set email alerts
|

Role of superoxide anions in the mediation of endothelium-dependent contractions.

Abstract: We designed experiments to characterize the role of superoxide anions in the mediation of endothelium-dependent contractions in isolated canine basilar arteries. Rings with and without endothelium were suspended for isometric tension recording in Krebs-Ringer bicarbonate solution bubbled with 94% Oj-6% CO 2 (37°C, pH 7.4). Radioimmunoassay was used to determine the levels of cyclic GMP and cyclic AMP. Calcium ionophore A23187 (1(T 9 to 1(T 6 mol/L) caused concentration-dependent contractions. The removal of en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(77 citation statements)
references
References 36 publications
5
71
0
1
Order By: Relevance
“…In addition, O 2 Ϫ might act as a direct venoconstrictor, consistent with previous demonstrations of its vasoconstrictor properties. 21,22 In contrast, baseline O 2 Ϫ levels in sham rats were apparently too low to be scavenged by tempol, which did not shift the ET-1-induced venoconstriction curve rightward in vessels from sham rats. The rationale of using ET-1 at a concentration of 10 Ϫ9 mol/L to stimulate O 2 Ϫ was based on our experimental observations that venous O 2 Ϫ levels produced by 10 Ϫ9 mol/L ET-1 in normal rats have already exceeded those found in DOCA-salt rats.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition, O 2 Ϫ might act as a direct venoconstrictor, consistent with previous demonstrations of its vasoconstrictor properties. 21,22 In contrast, baseline O 2 Ϫ levels in sham rats were apparently too low to be scavenged by tempol, which did not shift the ET-1-induced venoconstriction curve rightward in vessels from sham rats. The rationale of using ET-1 at a concentration of 10 Ϫ9 mol/L to stimulate O 2 Ϫ was based on our experimental observations that venous O 2 Ϫ levels produced by 10 Ϫ9 mol/L ET-1 in normal rats have already exceeded those found in DOCA-salt rats.…”
Section: Discussionmentioning
confidence: 92%
“…It has been reported that increased arterial O 2 Ϫ contributes to vasoconstriction by inactivating NO in both animals and humans with cardiovascular diseases, including hypertension. [1][2][3][21][22][23] Arterial O 2 Ϫ levels are markedly increased in DOCA-salt hypertension, a model with low plasma renin but high arterial ET-1 levels. 9 -14 However, it was not clear whether ET-1 also elevates venous O 2 Ϫ levels in this model.…”
Section: Discussionmentioning
confidence: 99%
“…These findings could be because of multiple sources of ROS and COXs are present in the cerebral vessels and in the surrounding neural tissues and astrocytes , releasing both constrictor and dilator factors (Cosentino et al, 1994;Wei et al, 1996). Thus, in vivo administration of drugs generating or inhibiting ROS production could activate several opposing vasomotor mechanisms.…”
Section: Mechanisms Mediating Flow-induced Constriction Of Cerebral Amentioning
confidence: 99%
“…26,64 In addition, O − 2 can act as a vasoconstrictor. [65][66][67][68] Nicotinamide adenine dinucleotide (NADH) dehydrogenase, a mitochondrial enzyme of the respiratory chain, seems to be a major source of O − 2 .…”
Section: Role Of Oxidative Stress In Hypertensionmentioning
confidence: 99%